(untitled) (Journal of Fiber Bioengineering and Informatics, 2009)
New quaternary ammonium compound, 6-(1-anthraquinonylamino) hexyldi methylammonium bromide (AHDDAB) was synthesized by 1-aminoanthraquinone with dimethyl dodecyl amine via hexamethylene spacer, antimicrobial activity was investigated. Results indicate that the new quaternary ammonium salt was successfully treated on PET surfaces by exhaustion method as in dyeing, and durable antimicrobial finish of PET was also investigated. New QAC was exhausted on PET fabric without any aid of chemical auxiliary even though it is water- soluble. Since AHDDAB is soluble in water, and the anthraquinonyl moiety of compound could anchor on PET surface, and the antimicrobial part orientates outwards, the results indicate that the durability of PET treated with AHDDAB was good enough to maintain the initial properties even after 30 repeated launderings. The fastness of PET treated with AHDDAB after 30 repeated launderings in anionic commercial detergent is good enough to show colony reduction above 70% against S, aureus and K, pneumoniae. The results mentioned above would suggest that test fabrics finished with AHDDAB could be valuable in the development of the field of antimicrobial fabrics, and could contribute considerably to better hygiene of all textiles in general.